Вакуумне подвійне променезаломлення в надкритичному магнітному полі - Diachenko, M.; Novak, O.; Kholodov, R. (Publishing house "Academperiodika", 2019)
The birefringence effect in vacuum in strong magnetic fields has been considered. The polarization tensor in a constant external magnetic field is analyzed in the framework of quantum field theory and on the basis of the electron Green’s function calculated as the sum over the Landau levels. The case of the lowest Landau levels for photons with the energies below the electron-positron pair creation threshold is considered, and the corresponding refractive indices of the physical vacuum for anomalous and normal waves are determined.